Introduction to Wireless Communication Circuits. - Farzaneh, Forouhar (River Publishers series in circuits and systems., 2018)
Over the past decade, tremendous development of Wireless Communications has changed human life and engineering. Considerable advancement has been made in design and architecture of related RF and microwave circuits. Introduction to Wireless Communication Circuits focusses on special circuits dedicated to the RF level of wireless communications. From oscillators to modulation and demodulation, and from mixers to RF and power amplifier circuits, all are presented in a sequential manner. A wealth of analytical relations is provided in the text alongside various worked out examples. Related problem sets are given at the end of each chapter. Basic concepts of RF Analog Circuit Design are developed in the book.